Hydrogen-corrosion-resistant coating material for hydrogen-rich electrolyte environment and preparation method of hydrogen-corrosion-resistant coating material

By adhering coating materials with components such as nickel-cobalt alloy layer and alumina-silicon carbide composite ceramic particles on the surface of the metal matrix, the existing hydrogen-resistant coating materials are easily peeled off, broken and complex processes in hydrogen-rich environments, and efficient anti-hydrogen corrosion, wear resistance and hydrogen embrittlement resistance are achieved, extending the service life of the equipment.

CN119530693APending Publication Date: 2025-02-28HAINAN UNIV

Patent Information

Application Number
CN202411721126.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing hydrogen-resistant corrosion coating materials have problems such as peeling, breaking, complex process, high cost and difficulty in precise control of coating thickness in hydrogen-rich environments, resulting in mechanical performance degradation and safety hazards in equipment during long-term use.

Method used

Coating materials using nickel-cobalt alloy layer, alumina and silicon carbide composite ceramic particles, rare earth elements yttrium oxide and cerium oxide, inorganic silicate binder, dispersant and crosslinking agent are adhered to the surface of the metal matrix through plasma spraying, cold spraying or electrodeposition processes to form a dense and uniform coating.

Benefits of technology

The coating material exhibits excellent corrosion resistance, wear resistance and hydrogen embrittlement resistance in a hydrogen-rich electrolyte environment, extending the service life of the equipment, reducing maintenance costs, and is suitable for industrial equipment under high temperature and high pressure conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530693A_ABST
    Figure CN119530693A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrogen-corrosion-resistant coating material for a hydrogen-rich electrolyte environment and a preparation method thereof, and relates to the technical field of hydrogen-corrosion-resistant coating materials, the coating material comprises the following components by weight: a metal matrix reinforcing material: 30%-50% of nickel and 5%-10% of cobalt; the ceramic particles comprise 10%-20% of aluminum oxide and 5%-15% of The coating material disclosed by the invention shows excellent corrosion resistance, wear resistance and hydrogen embrittlement resistance in a hydrogen-rich electrolyte environment. The nickel-cobalt alloy layer is kept stable at high temperature and high pressure, hydrogen permeation is blocked, and material degradation is prevented. Aluminum oxide and silicon carbide improve the hardness and wear resistance of the coating, and the coating is kept intact in temperature circulation. The rare earth elements yttrium oxide and cerium oxide enhance the oxidation resistance and hydrogen embrittlement resistance. And the dispersing agent and the cross-linking agent further improve the uniformity, compactness and adhesion of the coating, so that the coating is suitable for industrial parts in high-pressure and high-stress environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen corrosion resistant coating materials, and in particular to a hydrogen corrosion resistant coating material for use in a hydrogen-rich electrolyte environment and a preparation method thereof. Background Art

[0002] The application of hydrogen in industry is becoming more and more extensive, but in a hydrogen-rich environment, hydrogen atoms can penetrate the microstructure of metals or other materials, which can cause hydrogen embrittlement and hydrogen corrosion. This corrosion not only reduces the mechanical properties of the equipment, but also causes failure of key components, causing major safety hazards. Therefore, how to improve the corrosion resistance of materials in hydrogen-rich environments has become an important research direction in the field of materials. Hydrogen corrosion-resistant coating materials form a protective layer on the surface of the substrate to prevent the penetration of hydrogen atoms, thereby extending the service life of the material. In the prior art, materials widely used for hydrogen corrosion resistance include metal plating, ceramic coatings, and composite coatings.

[0003] Problems in the prior art:

[0004] However, existing hydrogen corrosion resistant coating materials still have many shortcomings in practical applications. First, although traditional metal coatings can block hydrogen penetration to a certain extent, they are prone to peeling and breaking in long-term hydrogen-rich environments, losing their protective effect. Although ceramic coatings have high corrosion resistance, they are prone to cracking in high and low temperature cycling environments due to the large difference in thermal expansion coefficient with the metal substrate. In addition, the process of composite coatings is complex, the preparation cost is high, and the coating thickness is difficult to accurately control. In practical applications, it is often difficult to meet the needs of complex working conditions.

[0005] In summary, there is an urgent need for a more efficient, durable and easy-to-apply hydrogen corrosion resistant coating material to improve the durability and safety of equipment in hydrogen-rich environments.

[0006] The above information disclosed in this Background section is only for enhancement of understanding of the background of the present disclosure and therefore it may contain information that does not form the prior art that is already known to one of ordinary skill in the art. Summary of the invention

[0007] The object of the present invention is to provide a hydrogen corrosion resistant coating material for a hydrogen-rich electrolyte environment and a preparation method thereof, wherein the coating material exhibits excellent corrosion resistance, wear resistance and hydrogen embrittlement resistance in a hydrogen-rich electrolyte environment. The nickel-cobalt alloy layer provides structural stability under high temperature and high pressure, effectively blocks the penetration of hydrogen atoms, prevents hydrogen embrittlement and material degradation, and reduces maintenance costs. The composite coating of aluminum oxide and silicon carbide improves hardness and wear resistance, reduces the friction coefficient, and remains intact without peeling during temperature cycles. The doping of rare earth elements yttrium oxide and cerium oxide enhances the oxidation resistance and hydrogen embrittlement resistance of the coating, and is suitable for high-pressure hydrogen environments such as fuel cells. Through the use of dispersants and cross-linking agents, the uniformity, density and adhesion of the coating are further improved, and it remains stable under high pressure, and is suitable for high-stress industrial components to solve the problems in the above-mentioned background technology.

[0008] In order to achieve the above object, the present invention provides the following technical solution: a hydrogen corrosion resistant coating material for a hydrogen-rich electrolyte environment, the coating material comprising the following components in weight percentage:

[0009] Metal matrix reinforcement material: nickel (Ni) 30%-50%, cobalt (Co) 5%-10%;

[0010] Ceramic particles: alumina (Al2O3) 10%-20%, silicon carbide (SiC) 5%-15%;

[0011] Rare earth element dopants: yttrium oxide (Y2O3) 1%-5%, cerium oxide (CeO2) 0.5%-3%;

[0012] Binder: inorganic silicate 5%-10%;

[0013] Dispersant: phosphate ester or polyacrylate 0.5%-2%;

[0014] Cross-linking agent: titanate or silane coupling agent 0.5%-2%;

[0015] Anticorrosive agent: nano titanium dioxide (TiO2) 1%-3%;

[0016] The coating material is attached to the surface of the metal substrate by plasma spraying, cold spraying or electrodeposition process to form a dense and uniform coating, which is used to prevent hydrogen penetration and corrosion in hydrogen-rich electrolyte.

[0017] Preferably, the alloy layer formed by nickel (Ni) and cobalt (Co) can maintain structural stability under high temperature and high pressure environments and enhance the adhesion between the substrate and the coating.

[0018] Preferably, the ceramic particles of aluminum oxide (Al2O3) and silicon carbide (SiC) can provide wear resistance in hydrogen-rich environments and reduce the risk of coating cracking during high and low temperature cycles.

[0019] Preferably, the rare earth elements yttrium oxide (Y2O3) and cerium oxide (CeO2) can effectively inhibit the intergranular corrosion of the coating during long-term use and improve the material's anti-oxidation and anti-hydrogen embrittlement properties.

[0020] Preferably, the inorganic silicate used as the binder can exist stably in an electrochemical environment and provide high-strength adhesion.

[0021] Preferably, the dispersant in the coating material improves the uniformity and density of the coating by reducing agglomeration between particles, thereby reducing the risk of hydrogen penetration.

[0022] Preferably, the cross-linking agent connects the coating material and the substrate by forming chemical bonds, further improving the mechanical strength and durability of the coating.

[0023] Preferably, nano titanium dioxide (TiO2) as an anti-corrosion aid can improve the UV resistance of the coating and further enhance the anti-corrosion effect in the electrolyte.

[0024] A method for preparing a hydrogen corrosion resistant coating material comprises the following steps:

[0025] Surface pretreatment: Use sandblasting or chemical etching to clean the surface of the metal substrate;

[0026] Coating preparation: Mix the coating materials evenly and attach them to the substrate surface using plasma spraying, cold spraying or electrodeposition processes;

[0027] Post-treatment: Heat treatment at 200℃ to 400℃ to improve the density and adhesion of the coating.

[0028] In the above technical solution, the technical effects and advantages provided by the present invention are:

[0029] The coating material of the present invention exhibits excellent corrosion resistance in a hydrogen-rich electrolyte environment through the structural design of the nickel-cobalt alloy layer. The alloy combination of nickel and cobalt can remain stable under high temperature and high pressure, prevent the coating from peeling and breaking, and extend the service life of the equipment. The high density of this coating effectively blocks the penetration of hydrogen atoms, prevents hydrogen embrittlement and material degradation. This feature makes it particularly suitable for industrial equipment under high temperature and high pressure conditions, ensures the stable operation of the equipment, and reduces maintenance costs and the risk of unexpected downtime.

[0030] The composite coating of aluminum oxide and silicon carbide ceramic particles in the present invention exhibits excellent wear resistance and temperature cycle resistance in a hydrogen-rich environment. The addition of aluminum oxide and silicon carbide particles not only increases the hardness of the coating, but also effectively reduces the friction coefficient. The sliding friction test shows that the friction coefficient of the coating is only 0.15, which is much lower than 0.35 of the untreated substrate, significantly reducing the wear of the equipment during operation. At the same time, after 100 high and low temperature cycle tests, only a small amount of microcracks appeared on the surface of the coating and it did not peel off, proving that it can cope with complex temperature change environments. This wear resistance and temperature cycle resistance make the coating suitable for long-term use of mechanical parts in harsh environments, extending the service life of the equipment.

[0031] The rare earth elements yttrium oxide (Y2O3) and cerium oxide (CeO2) added to the coating material significantly improve the material's oxidation resistance and hydrogen embrittlement resistance. In a 300-hour accelerated corrosion test in a hydrogen-rich electrolyte environment, the corrosion resistance of the coating sample doped with rare earth elements reached 1200 ohm cm 2 , which is 2.5 times higher than that of the undoped sample. Microscopic analysis shows that rare earth elements can inhibit intergranular corrosion and prevent the coating from structural instability under high temperature and high pressure. In addition, rare earth doping also enhances the coating's resistance to hydrogen embrittlement, reduces the propagation of microcracks in the coating, and improves the long-term stability of the material in a hydrogen-rich environment. Therefore, the coating is particularly suitable for equipment that is exposed to high temperature and high pressure hydrogen environments for a long time, such as fuel cells and chemical equipment.

[0032] The coating material of the present invention exhibits excellent uniformity and adhesion through the rational application of dispersants and crosslinking agents. Dispersants (such as phosphate esters) can effectively reduce the agglomeration between particles and improve the compactness of the coating, thereby reducing the risk of hydrogen atom penetration. In the hydrogen permeation test, the hydrogen permeation rate of the coating sample was 1.2×10 -6 mol / m 2 / s, which is 65% lower than that of the untreated sample. At the same time, the cross-linking agent (such as silane coupling agent) forms a strong chemical bond between the coating and the substrate, so that the coating can still maintain adhesion under high pressure and avoid peeling and delamination. When tested under a pressure of 30MPa, the coating structure remains intact. This feature makes the coating suitable for key components in high-stress and high-corrosion environments, ensuring long-term and stable operation of the equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.

[0034] Figure 1The present invention is a flow chart of the method for preparing a hydrogen corrosion resistant coating material. DETAILED DESCRIPTION

[0035] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the examples set forth herein; rather, these example embodiments are provided so that the description of the present disclosure will be more comprehensive and complete, and the concept of the example embodiments will be fully conveyed to those skilled in the art.

[0036] The present invention provides a hydrogen corrosion resistant coating material for use in a hydrogen-rich electrolyte environment, the coating material comprising the following components in weight percentage:

[0037] Metal matrix reinforcement material: nickel (Ni) 30%-50%, cobalt (Co) 5%-10%;

[0038] Ceramic particles: alumina (Al2O3) 10%-20%, silicon carbide (SiC) 5%-15%;

[0039] Rare earth element dopants: yttrium oxide (Y2O3) 1%-5%, cerium oxide (CeO2) 0.5%-3%;

[0040] Binder: inorganic silicate 5%-10%;

[0041] Dispersant: phosphate ester or polyacrylate 0.5%-2%;

[0042] Cross-linking agent: titanate or silane coupling agent 0.5%-2%;

[0043] Anticorrosive agent: nano titanium dioxide (TiO2) 1%-3%;

[0044] The coating material is attached to the surface of the metal substrate by plasma spraying, cold spraying or electrodeposition process to form a dense and uniform coating, which is used to prevent hydrogen penetration and corrosion in hydrogen-rich electrolyte.

[0045] The alloy layer formed by nickel (Ni) and cobalt (Co) can maintain structural stability under high temperature and high pressure environment and enhance the adhesion between the substrate and the coating. Ceramic particles of aluminum oxide (Al2O3) and silicon carbide (SiC) can provide wear resistance in hydrogen-rich environment and reduce the risk of coating cracking in high and low temperature cycles. Rare earth elements yttrium oxide (Y2O3) and cerium oxide (CeO2) can effectively inhibit the intergranular corrosion of the coating during long-term use and improve the material's anti-oxidation and anti-hydrogen embrittlement properties. The inorganic silicate used as the binder can exist stably in the electrochemical environment and provide high-strength adhesion. The dispersant in the coating material improves the uniformity and density of the coating by reducing the agglomeration between particles, thereby reducing the risk of hydrogen penetration. The cross-linking agent connects the coating material and the substrate by forming chemical bonds, further improving the mechanical strength and durability of the coating. Nano titanium dioxide (TiO2) as an anti-corrosion additive can improve the UV resistance of the coating and further enhance the anti-corrosion effect in the electrolyte.

[0046] A method for preparing a hydrogen corrosion resistant coating material comprises the following steps:

[0047] Surface pretreatment: Use sandblasting or chemical etching to clean the surface of the metal substrate;

[0048] Coating preparation: The coating materials are mixed uniformly and attached to the substrate surface using plasma spraying, cold spraying or electrodeposition processes;

[0049] Post-treatment: Heat treatment at 200℃ to 400℃ to improve the density and adhesion of the coating.

[0050] Example 1: Test of hydrogen corrosion resistance of nickel-cobalt alloy layer;

[0051] This example studies the hydrogen corrosion resistance of the nickel-cobalt alloy layer in a hydrogen-rich environment. The alloy material of 40% nickel and 8% cobalt is used to attach the coating to the surface of the stainless steel substrate through a plasma spraying process. The substrate surface is pretreated and a sandblasting process is used to remove oxides and contaminants to ensure the adhesion of the coating. The coated sample is heat treated at 250°C for 2 hours to improve the density and stability of the coating.

[0052] During the experiment, the sample was placed in a hydrogen-rich electrolyte environment, the temperature of which was maintained at 85°C and the pressure was 5MPa, and the test time was 1000 hours. The electrolyte simulated actual industrial conditions and its main components included 10wt% potassium hydroxide (KOH) and 5wt% ammonium sulfate (NH4)2SO4. During the test, the sample was taken out for observation every 100 hours, and the weight change and surface morphology of the coating were measured.

[0053] The results show that after 1000 hours of corrosion test, the mass loss of the coating was only 0.02%, while the mass loss of the uncoated stainless steel substrate under the same conditions reached 0.35%, indicating that the nickel-cobalt alloy layer has a significant inhibitory effect on hydrogen corrosion. Microstructural analysis shows that there are no cracks or peeling on the coating surface, and the interface between the grains remains intact, proving that the coating has good adhesion under long-term high temperature and high pressure. Electrochemical tests further show that the corrosion potential of the sample in a hydrogen-rich environment is 200mV higher than that of the uncoated sample, and the corrosion current density is reduced by 60%. These data fully verify the excellent corrosion resistance and structural stability of the nickel-cobalt alloy layer in high temperature and hydrogen-rich environments.

[0054] Example 2: Wear resistance and heat resistance of aluminum oxide-silicon carbide composite coating;

[0055] This example tests the wear resistance and heat resistance of a composite ceramic particle coating of aluminum oxide (Al2O3) and silicon carbide (SiC) in a hydrogen-rich environment. The coating material used is a mixture of 15% aluminum oxide and 10% silicon carbide, which is applied to an aluminum alloy substrate by a cold spraying process. The cold spraying process is completed at room temperature, effectively avoiding damage to the substrate by high temperature. The sprayed sample is heat treated at 300°C for 3 hours to increase the bonding strength between the coating and the substrate and make the coating denser.

[0056] In order to evaluate the temperature cycle resistance of the coating, the sample underwent 100 temperature cycles, with the temperature range of each cycle ranging from 20°C to 80°C and each stage lasting 10 minutes. The coating surface before and after the temperature cycle was observed under a microscope, and it was found that after 100 cycles, only a small number of microcracks appeared on the coating surface, and the crack width remained below 10 microns, which did not affect the overall structure of the coating. In the wear resistance test, the sample was subjected to a sliding friction test with a stainless steel disc using a wear tester, with a vertical force of 10N and a sliding distance of 1000 meters. The test results show that the friction coefficient of the composite ceramic coating is 0.15, which is significantly lower than the friction coefficient of the uncoated substrate (0.35), showing excellent wear resistance.

[0057] In addition, in order to further test the performance of the coating in a hydrogen environment, the sample was placed in a 5MPa hydrogen-rich electrolyte environment for 200 hours. After the test, it was found that the coating structure remained intact, there was no sign of peeling, and the surface wear depth was controlled within 3 microns. This experiment shows that the combination of aluminum oxide and silicon carbide not only improves the wear resistance of the coating, but also effectively copes with the stress caused by high and low temperature cycles.

[0058] Example 3: Anti-oxidation and anti-corrosion properties of rare earth element doped coatings;

[0059] In this example, the effect of yttrium oxide (Y2O3) and cerium oxide (CeO2) doping on the corrosion resistance of the coating was studied. First, a coating material containing 2% yttrium oxide and 1.5% cerium oxide was applied to a carbon steel substrate using an electrodeposition process. The deposition process was carried out in a nickel salt solution at 60°C, and the current density was controlled to 2A / dm 2 , the deposition time was 1 h. Subsequently, the samples were heat treated at 300 °C to improve the adhesion and density of the coating.

[0060] To verify the anti-oxidation and anti-corrosion properties of the coating, the sample was subjected to an accelerated corrosion test in an electrolyte environment at 10 MPa pressure and 90°C for 300 hours. After the test, the corrosion resistance was measured by electrochemical impedance spectroscopy (EIS). The experimental results showed that the corrosion resistance of the coating sample doped with rare earth elements reached 1200 ohm cm 2 , while the control sample without rare earth element doping has only 480 ohm·cm 2 , which was increased by about 2.5 times. In addition, scanning electron microscopy analysis showed that there was no obvious sign of grain boundary corrosion on the surface of the rare earth-doped coating, confirming the anti-oxidation and anti-corrosion effects of rare earth elements under high temperature and high pressure.

[0061] Example 4: Dispersants and cross-linking agents improve the uniformity and durability of coatings;

[0062] This example uses 1% phosphate as a dispersant and 1% silane coupling agent as a cross-linking agent to study their role in improving coating uniformity and durability. First, these additives are uniformly mixed with other coating materials and applied to the surface of the titanium alloy substrate through a plasma spraying process. The sample is heat treated in a furnace at 350°C for 2 hours to enhance the mechanical properties of the coating.

[0063] In the hydrogen permeation test, the sample was exposed to a hydrogen-rich electrolyte at 80°C and 5 MPa for 500 hours. The permeability was then measured using a hydrogen permeation detector. The test results showed that the hydrogen permeation rate of the coating was 1.2×10 -6 mol / m 2 / s, while the permeation rate of the untreated sample was 3.5×10 -6 mol / m 2 / s, a decrease of about 65%. In addition, the sample did not show peeling in the compression test under 30MPa pressure, proving the high durability and excellent adhesion of the coating.

[0064] Microscopic analysis showed that the use of dispersants reduced the agglomeration between particles, making the coating more uniform and dense. The cross-linking effect of silane coupling agents enhanced the chemical bonding between the coating material and the substrate, improving the overall mechanical strength. This experiment shows that by properly selecting dispersants and cross-linkers, the performance of the coating can be further optimized to cope with harsh industrial environments.

[0065] These embodiments show the performance of hydrogen corrosion resistant coating materials under different conditions. The experimental results show that these coatings not only have excellent hydrogen permeation resistance and corrosion resistance, but also show excellent performance in wear resistance, heat resistance and long-term stability. These data provide strong support for the practical application of the present invention.

[0066] The coating material of the present invention exhibits excellent corrosion resistance in a hydrogen-rich electrolyte environment through the structural design of the nickel-cobalt alloy layer. The alloy combination of nickel and cobalt can remain stable under high temperature and high pressure, prevent the coating from peeling and breaking, and extend the service life of the equipment. Test data show that after 1000 hours of hydrogen-rich environment testing, the mass loss of the coating is only 0.02%, which is much lower than the 0.35% of the uncoated material. The high density of this coating effectively blocks the penetration of hydrogen atoms, preventing hydrogen embrittlement and material degradation. This feature makes it particularly suitable for industrial equipment under high temperature and high pressure conditions, ensuring the stable operation of the equipment and reducing maintenance costs and the risk of unexpected downtime.

[0067] The composite coating of aluminum oxide and silicon carbide ceramic particles in the present invention exhibits excellent wear resistance and temperature cycle resistance in a hydrogen-rich environment. The addition of aluminum oxide and silicon carbide particles not only increases the hardness of the coating, but also effectively reduces the friction coefficient. The sliding friction test shows that the friction coefficient of the coating is only 0.15, which is much lower than 0.35 of the untreated substrate, significantly reducing the wear of the equipment during operation. At the same time, after 100 high and low temperature cycle tests, only a small amount of microcracks appeared on the surface of the coating and it did not peel off, proving that it can cope with complex temperature change environments. This wear resistance and temperature cycle resistance make the coating suitable for long-term use of mechanical parts in harsh environments, extending the service life of the equipment.

[0068] The rare earth elements yttrium oxide (Y2O3) and cerium oxide (CeO2) added to the coating material significantly improve the material's oxidation resistance and hydrogen embrittlement resistance. In a 300-hour accelerated corrosion test in a hydrogen-rich electrolyte environment, the corrosion resistance of the coating sample doped with rare earth elements reached 1200 ohm cm 2, which is 2.5 times higher than that of the undoped sample. Microscopic analysis shows that rare earth elements can inhibit intergranular corrosion and prevent the coating from structural instability under high temperature and high pressure. In addition, rare earth doping also enhances the coating's resistance to hydrogen embrittlement, reduces the propagation of microcracks in the coating, and improves the long-term stability of the material in a hydrogen-rich environment. Therefore, the coating is particularly suitable for equipment that is exposed to high temperature and high pressure hydrogen environments for a long time, such as fuel cells and chemical equipment.

[0069] Through the rational application of dispersants and crosslinking agents, the coating material of the present invention exhibits excellent uniformity and adhesion. Dispersants (such as phosphate esters) can effectively reduce the agglomeration between particles and improve the compactness of the coating, thereby reducing the risk of hydrogen atom penetration. In the hydrogen permeation test, the hydrogen permeation rate of the coating sample was 1.2×10 -6 mol / m 2 / s, which is 65% lower than that of the untreated sample. At the same time, the cross-linking agent (such as silane coupling agent) forms a strong chemical bond between the coating and the substrate, so that the coating can still maintain adhesion under high pressure and avoid peeling and delamination. When tested under a pressure of 30MPa, the coating structure remains intact. This feature makes the coating suitable for key components in high-stress and high-corrosion environments, ensuring long-term and stable operation of the equipment.

[0070] The above description is only by way of illustration of certain exemplary embodiments of the present invention. It is undoubted that those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the above drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.

Claims

1. A hydrogen corrosion resistant coating material for use in a hydrogen-rich electrolyte environment, characterized in that: The coating material includes the following components in weight percentage: Metal matrix reinforcement material: nickel 30%-50%, cobalt 5%-10%; Ceramic particles: 10%-20% alumina, 5%-15% silicon carbide; Rare earth element dopants: yttrium oxide 1%-5%, cerium oxide 0.5%-3%; Binder: inorganic silicate 5%-10%; Dispersant: phosphate ester or polyacrylate 0.5%-2%; Cross-linking agent: titanate or silane coupling agent 0.5%-2%; Anticorrosive agent: nano titanium dioxide 1%-3%; The coating material is attached to the surface of the metal substrate by plasma spraying, cold spraying or electrodeposition process to form a dense and uniform coating, which is used to prevent hydrogen penetration and corrosion in hydrogen-rich electrolyte.

2. A hydrogen corrosion resistant coating material for use in a hydrogen-rich electrolyte environment according to claim 1, characterized in that: The alloy layer formed by nickel and cobalt maintains structural stability under high temperature and high pressure environments and enhances the adhesion between the substrate and the coating.

3. A hydrogen corrosion resistant coating material for use in a hydrogen-rich electrolyte environment according to claim 1, characterized in that: Ceramic particles of aluminum oxide and silicon carbide provide wear resistance in hydrogen-rich environments and reduce the risk of coating cracking during high and low temperature cycles.

4. A hydrogen corrosion resistant coating material for use in a hydrogen-rich electrolyte environment according to claim 1, characterized in that: The rare earth elements yttrium oxide and cerium oxide effectively inhibit the intergranular corrosion of the coating during long-term use and improve the material's anti-oxidation and anti-hydrogen embrittlement properties.

5. A hydrogen corrosion resistant coating material for use in a hydrogen-rich electrolyte environment according to claim 1, characterized in that: The inorganic silicate used in the binder is stable in the electrochemical environment and provides high-strength adhesion.

6. A hydrogen corrosion resistant coating material for use in a hydrogen-rich electrolyte environment according to claim 1, characterized in that: Dispersants in coating materials can improve the uniformity and density of coatings and reduce the risk of hydrogen permeation by reducing agglomeration between particles.

7. A hydrogen corrosion resistant coating material for use in a hydrogen-rich electrolyte environment according to claim 1, characterized in that: Crosslinkers connect coating materials to the substrate by forming chemical bonds, improving the mechanical strength and durability of the coating.

8. A hydrogen corrosion resistant coating material for use in a hydrogen-rich electrolyte environment according to claim 1, characterized in that: Nano titanium dioxide as an anti-corrosion agent can improve the UV resistance of the coating and further enhance the anti-corrosion effect in the electrolyte.

9. A method for preparing a hydrogen corrosion resistant coating material, characterized in that: The steps include: Surface pretreatment: Use sandblasting or chemical etching to clean the surface of the metal substrate; Coating preparation: Mix the coating materials evenly and attach them to the substrate surface using plasma spraying, cold spraying or electrodeposition processes; Post-treatment: Heat treatment at 200℃ to 400℃ to improve the density and adhesion of the coating.

Citation Information

Patent Citations

  • Preparation method of NiCr / Al2O3 composite coating

    CN108359927A

  • Hydrogen-resistant coating based on cathode plasma electrolytic deposition and preparation method thereof

    CN111676499A

  • Hydrogen embrittlement resistant composite coating for bipolar plate of PEM electrolytic cell and preparation method thereof

    CN118773608A

Cited By

  • Suspension valve disc system of immersed liquid hydrogen pump

    CN119878520A